Education 4.0 and the skills of the future: are Nova SBE graduates prepared? - Mangericão, Tamara (2019)
This paper examines the effects of the labor market by the Fourth Digital Revolution, and how they will impact Higher Education Institutes, in particular. “Education 4.0” is the answer to the needs of “Industry 4.0”, and the consequent importance of understanding what are the skills that are necessary for the future graduate. Additionally, this paper also has the purpose of understanding if graduates from Nova SBE feel that they are prepared with the skills that will be necessary for the future. Differences in perceptions were found across the type of master programs regarding the categories of Higher Cognitive, Social and Emotional, and Technological skills. The main finding of this paper is the urgent need for business schools to rethink their design for the experience of the future, in order to correspond to the fast-changing needs of all important stakeholders.